PENGARUH TEACHING FACTORY TERHADAP MINAT BERWIRAUSAHA SMK NEGERI 1 DUDUKSAMPEYAN - Djoko Suwito; Arni Sulistyowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teaching Factory (Tefa) is an educational model that integrates practical industry-based learning into vocational schools. This research aims to analyze the impact of Teaching Factory implementation on students' entrepreneurial interest at SMKN 1 Duduksampeyan. The study employs a quantitative approach with a descriptive research design. Data were collected through questionnaires distributed to students from vocational programs Industrial Mechanical Engineering. The results indicate that Teaching Factory significantly influences students' entrepreneurial interest, with an average score of 82.85%, placing it in the "Highly Influential" category. Additionally, 78% of students expressed motivation to start their own businesses after participating in the program. These findings highlight the effectiveness of Teaching Factory in fostering entrepreneurial aspirations among vocational students.